Production Efficiency of Enbal (Cassava) Using Hydraulic Press Equipment in the Enbal Processing Group in Ibra Village, Southeast Maluku Regency - Marasabessy, Ismael; Sudirjo, Fien; K.Hamid, Syahibul; Irmawaty, Yuni (Agrikan Jurnal Agribisnis Perikanan, 2020)
The purpose of this activity is to increase the efficiency in production process by applying screw press equipment and improving sanitation and hygiene in its production. The method of implementing activities uses discussion and training techniques. The activity is carried out in three stages, firstly survey on condition and discussion with partners relates to the conditions of producing pressing enbal, secondly the manufacture of pressing tools, third is the application of pressing tools in production activities of partners. The results of the activity showed that the screw press was able to produce enough water of enbal / grated cassava so that it is drier than the traditional method. Press time becomes faster which only 12-15 minutes, whereas in the traditional way it takes 14-24 hours. The content of enbal’s water decreases very low, reaching 5-7%, the sanitation becomes better because the juice is no longer stagnant on the ground but is collected in a bucket, and the use of pressing tools is very practical. Likewise the HCN level is very low, less than 3mg / kg so the product is very safe for consumption. This screw press is very helpful in the efficiency of the production process of plate enbal (cassava plates) which is cleaner and healthier.